High spectral efficiency SSB-PAM-DD scheme with high linewidth tolerance - Dongxu LU; Xian ZHOU; Fei LIU; Jiahao HUO; Jinhui YUAN; Keping LONG (Tongxin xuebao)
For low-cost and high chromatic dispersion (CD) robustness single sideband (SSB) with direct detection (DD), three schemes of SSB with pulse amplitude modulation (PAM) were investigated.Among that, the highest spectral efficiency was achieved by the scheme of adding the frequency down-conversion at the transmitter.However, that scheme reduces the tolerance for laser linewidth.Hence, based on the character of the SSB-PAM signal, a DSP scheme was proposed, including a modified equalization algorithm with phase distortion immunity and blind phase search algorithm.The simulation results show that the modified scheme can tolerate 1 MHz linewidth for 112 Gbit/s SSB-PAM-DD, while the original scheme for SSB-PAM was only 100 kHz at the same bit error rate (BER) threshold.Therefore, the proposed scheme can achieve a high frequency efficiency, high linewidth tolerance, and low-cost SSB-PAM signaling transmission.